PELATIHAN PEMBUATAN ATRAKTAN ALAMI DARI TUMBUHAN AROMATIKA UNTUK PENGENDALIAN LALAT BUAH Bactrocera sp. PADA PERTANAMAN CABAI DI KECAMATAN SIGI BIROMARU - H, Humaira; Tasik, Selvi Banne; M., Masriatun (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Utilization of plants as botanical pesticides for the general public based on a health factor of the residues generated in the synthetic pesticides, but in reality many habits in the use of synthetic pesticides in the farm community is relatively difficult to remove. It was recognized in general pesticides are hazardous materials that may have negative effects on human health and environmental sustainability. Attention to the problem and its negative impact, then the control by using plant-based pesticides can be managed well at least as well as the active participation of the community. Some plant species have been reported to be pestisidal can be developed as a decoy fruit flies because they contain eugenol compounds to control fruit flies. Herb clove oil, basil plant extracts, and herbs viteks. eugenol -containing compounds have been reported and are often found growing in the highlands city of Palu can be used by the public. The purpose of this program is to train farmers PKMM make Natural attractant plants simply as a decoy fruit flies in an effort to improve the quantity and quality of chilli crop production in order to increase the income of farmers. PKMM implementation lasted for 4 months ie in April 2013 to July 2013. The method used is the method of education and training and demonstration plots conducted experiments with participatory approaches / PRA ( Participatory Rural Approach ) which target groups are actively involved from the beginning to the end of the program, including evaluation. Extension activities carried out in an effort to improve the knowledge, training and demonstration plots are being conducted in an effort to accelerate the process of technology transfer to the public. The results achieved are the target communities have learned the technique of making potions clove oil, basil plant extracts, and herbs viteks.secara simple as a decoy sehigga fruit flies can be developed into one of the small and medium enterprises ( SMEs ) in the target area in the form of program -making materials PKMM Decoy fruit flies with a cheaper price so that it can be reached by farmers.